Zinc Oxide Nanoparticles Catalyzed Condensation Reaction of Isocoumarins and 1,7-Heptadiamine in the Formation of Bis-Isoquinolinones - Varadhan Krishnakumar; Kesarla Mohan Kumar; Badal Kumar Mandal; Fazlur-Rahman Nawaz Khan (The Scientific World Journal)
The diversified bis-isoquinolinones were obtained in two steps, utilizing homophthalic acid and various acid chlorides providing 3-substituted isocoumarins in the first step which on further condensation with 1,7-heptadiamine involving C–N bond formation from the lactone in the presence of 10 mol% zinc oxide nanoparticles (ZnO NPs) (<150 nm) afforded the desired bis-isoquinolinones in high yield and purity. The synthesized compounds were then characterized using FTIR, 1H NMR, 13C NMR, and HRMS techniques.